2015
DOI: 10.1103/physrevb.92.085420
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of surface charging inLaAlO3/SrTiO3heterostructures

Abstract: The two-dimensional electron gas (2DEG) observed at the interface between LaAlO3 (LAO) and SrTiO3 (STO) is known to be very sensitive to the proximity of the LaAlO3 surface and the conditions to which the surface is exposed. We use first-principles calculations to study surface reconstructions on LAO films, taking into account that the LAO surface can be charged. The results for the charged surfaces and for the coupling between the surface and the 2DEG enable us to account not only for the behavior of the 2DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Some research efforts are still being made to explore a comprehensive model that can account for all the experimental phenomena in the LAO/STO HS. 12,13 Several possible explanations for this discrepancy have been proposed from various viewpoints. [12][13][14][15][16][17] For example, from density functional theory (DFT) calculations, Popović et al suggested that the transferred electrons are not only confined to the interfacial TiO 2 layer but also extend over several deeper TiO 2 layers, which dilutes the sheet carrier density.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research efforts are still being made to explore a comprehensive model that can account for all the experimental phenomena in the LAO/STO HS. 12,13 Several possible explanations for this discrepancy have been proposed from various viewpoints. [12][13][14][15][16][17] For example, from density functional theory (DFT) calculations, Popović et al suggested that the transferred electrons are not only confined to the interfacial TiO 2 layer but also extend over several deeper TiO 2 layers, which dilutes the sheet carrier density.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Several possible explanations for this discrepancy have been proposed from various viewpoints. [12][13][14][15][16][17] For example, from density functional theory (DFT) calculations, Popović et al suggested that the transferred electrons are not only confined to the interfacial TiO 2 layer but also extend over several deeper TiO 2 layers, which dilutes the sheet carrier density. 14 Using first-principles electronic structure calculations, Krishnaswamy et al proposed that the sheet carrier density of 3.3 Â 10 14 cm À2 is intrinsic to the LaO/TiO 2 interface in the LAO/ STO system, while the AlO 2 -terminated surface may transfer electrons from the 2DEG to the surface states, leading to a smaller sheet carrier density at the interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…71,72 The localized field is important in understanding localized processes at the interface. Recent studies have both measured experimentally 73 and predicted theoretically 74,75 the existence of such large electric fields at a water/oxide interface, an oxide surface, and oxide heterostructures, and their impact on the field-dependent properties such as local bonding interaction, dielectric constant, and 2D electron gas density. When these properties are of interest, accurate prediction of local electric field accounting for both perfect crystal contribution and defect contribution would be necessary.…”
Section: A Electrostatic Profilesmentioning
confidence: 99%
“…Other approaches treat the charged surface defects by introducing an additional dopant charge into the calculation and by applying a posteriori correction schemes to subtract the contributions of the compensating homogeneous background in the supercell. These approaches, however, neglect the effect of the electric field in the space charge region [35,36]. Kempisty and Krukowski presented a method to account for the electric field of the space charge region by manipulating the location and charge of passivating atoms on the back side of the slab [37][38][39][40], but did not translate the added charge into the bulk doping concentration.…”
Section: Introductionmentioning
confidence: 99%